Synthesis, in vitro Antimicrobial assay and Molecular Docking Studies of some new Symmetrical Bis-Schiff Bases and their 2-Azetidinones. - Sangar Ali Hassan; Media Noori Abdullah; Dara Muhammed Aziz (Zanco Journal of Pure and Applied Sciences, 2021)
Four membered cyclic amides that are a broadly utilized class of antimicrobial agents up to now. Moreover, Symmetrical Bis-Schiff bases constitute an extraordinary class of strained compounds with varied applications and building blocks for the synthesis of 2-Azetidinones antibiotics. Because of those over biological significance, this study concludes a versatile synthetic precursor for the synthesis of the new Symmetrical Bis-Schiff bases and 2-Azetidinones in an exceedingly high yield. 2-Azetidinones were synthesized through [2+2] dichloroketene-imine cycloaddition reaction. The structures of the synthesized compounds were characterized by FT-IR, 1H-NMR, and 13C-NMR. Additionally, the products were assayed against two antibacterial types Gram-positive (S. aureus) and Gram-negative (E. coli) microorganisms and two varieties of fungal strains A. niger, T. mentagrophytes by broth microdilution method. As a result, all synthesized compounds displayed good antimicrobial activities against resistant strains. Finally, molecular docking studies were explained the inhibitory activities for the new products with the target (PDB ID: 1MWU) methicillin acyl-Penicillin binding protein 2a from methicillin-resistant Staphylococcus aureus strain 27r at 2.60 Å resolution.